Emergency medicine pharmacotherapy compromises accuracy of plasma creatinine determination by enzyme-based methods: real-world clinical evidence and implications for clinical practice - Demlova, Regina; Kozakova, Sarka; Rihacek, Michal; Buckova, Dana; Horska, Katerina; Wiewiorka, Ondrej; Boucek, Lubos; Selingerova, Iveta; Podborska, Martina; Korberova, Alena; Mikuskova, Alena; Starha, Jiri; et al. (Frontiers in Medicine, 2024)
Background Assessment of kidney function in emergency settings is essential across all medical subspecialties. Daily assessment of patient creatinine results from emergency medical services showed that some deviated from expected values, implying drug-related interference. Methods Real-time clinical evaluation of an enzyme method (Roche CREP2) in comparison with the Jaffé gen. 2 method (Roche CREJ2) was performed. During the period of December 2022 and January 2023, we analyzed 8,498 patient samples, where 5,524 were heavily medicated STAT patient specimens, 500 were pediatric specimens, and 2,474 were from a distant general population in a different region using the same methods. Results In 109 out of 5,524 hospital specimens (1.97%, p < 0.001), the CREP2 value was apparently (25% or more) lower than CREJ2. Suspect interfering medication was found in a sample of 43 out of 46 reviewed patients where medication data were available. This phenomenon was not observed in the general population. Conclusion In a polymedicated urgent care hospital population, a creatinine enzyme method produces unreliable results, apparently due to multiple drug-related interferences.